Repeatability of artificial gravity tolerance times - Stead, T.; Blaber, A. P.; Divsalar, D. N.; Xu, D.; Tavakolian, K.; Evans, J.; Billette de Villemeur, R.; Bareille, M-P; Saloň, A.; Steuber, B.; Goswami, N. (Frontiers in Physiology, 2025)
IntroductionExposure to microgravity results in physiological deconditioning, including orthostatic intolerance. Artificial gravity (AG) from short-arm centrifuges is being tested in ground-based studies to counter these effects. Orthostatic tolerance testing with centrifuges before and after these spaceflight analogs could determine the efficacy of an AG countermeasure to orthostatic tolerance. However, there has not been an investigation on how long before analog testing AG orthostatic tolerance data would remain valid for such a study.MethodsA secondary analysis of two experiments involving AG orthostatic tolerance testing (starting at 0.6 for females and 0.8 Gz for males and increased by 0.1 Gz every 3 minutes until presyncope) conducted 7 months apart at MEDES revealed 4 male and 3 female participants who had taken part in both.ResultsComparisons of participants’ time to presyncope between the two tests using Lin’s concordance correlation coefficient (LCCC) showed a significant relationship in time to presyncope between the two test dates (LCCC = 0.98) for males but not for females (LCCC = −0.64). While the cardiovascular data from one female was unusable, the mean heart rate responses to increasing artificial gravity during the orthostatic tolerance procedure showed a strong linear correlation between the two tests for all other participants (all p < 0.008). The LCCC heart rate changes with centrifuge level varied across male participants from 0.61 to 0.97, suggesting that the high LCCC for time to presyncope was achieved with varied HR baselines between the two test dates.DiscussionThese findings indicate that time-to-presyncope tests may remain valid up to 7 months after the testing date for males. We highly recommend further study with larger numbers of male and female participants.